Effectiveness of Providing Counseling with Understanding Intercultural Communication - Kara, Raka Sutateon Ivanda Kara (International Journal of Multicultural Counseling and Development, 2024)
Cross-cultural counseling involves providing support to minority groups within various cultural contexts. It recognizes that counseling is a cultural exchange between the counselor and the client. Behaviors considered problematic and methods of adjustment vary across cultures, highlighting the importance of cultural sensitivity for effective counseling. Counselors must overcome cultural biases and possess skills that acknowledge and respect diverse cultural backgrounds. Intercultural communication occurs across nations, encompassing differences in norms, race, language, religion, education level, social status, and gender. It requires diplomatic approaches from individuals such as foreign students, international school teachers, and social workers. Understanding intercultural communication involves examining communication approaches, identifying barriers between cultures, and assessing how these barriers impact communication. During counseling sessions, it's crucial for counselors not only to understand the client's culture but also to recognize the individual cultural nuances of each client. Failing to do so may lead to cultural insensitivity, lack of empathy, and the imposition of the counselor's cultural values onto the client.